2008
DOI: 10.1007/s00128-007-9310-8
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of EDTA in Chromium (III–VI) Toxicity on Marine Intertidal Crab (Petrolisthes laevigatus)

Abstract: Chromium poses a potential threat to coastal ecosystems. We used standard toxicity bioassays (semi-static, chronic) to evaluate EDTA as a chelating agent for reducing trivalent and hexavalent chromium toxicity on Petrolisthes laevigatus. Crab survival decreased linearly with increased chromium concentrations and dropped significantly beginning at 40 mg/L Cr (VI) and 80 mg/L Cr (III). No significant differences were observed with Cr (III) + EDTA as compared with untreated controls. Cr (VI) toxicity was greater … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The toxicity of Cr 2 O 3 is lower than that of hexavalent chromium (Cr(VI)) compounds such as CrO 3 , which is water soluble and a strong oxidant (Barceloux,1999; Hininger et al,2007; Urrutia et al,2008). There have been many investigations focusing on the carcinogenicity of hexavalent chromium (De Flora and Wetterhahn,1989; Holmes et al,2008).…”
Section: Introductionmentioning
confidence: 99%
“…The toxicity of Cr 2 O 3 is lower than that of hexavalent chromium (Cr(VI)) compounds such as CrO 3 , which is water soluble and a strong oxidant (Barceloux,1999; Hininger et al,2007; Urrutia et al,2008). There have been many investigations focusing on the carcinogenicity of hexavalent chromium (De Flora and Wetterhahn,1989; Holmes et al,2008).…”
Section: Introductionmentioning
confidence: 99%
“…No significant differences were observed with Cr (III) + EDTA as compared with untreated controls. Cr (VI) toxicity was greater than of Cr (III), with low individual survival rates [47].…”
Section: Chromiummentioning
confidence: 92%
“…Excess amounts of ROS can cause cell death by damaging DNA and RNA, inactivating enzymes, oxidizing proteins, and causing lipid peroxidation ( Srivastava et al., 2021 ). Despite this fact, it has been found that Cr (III) is less harmful than Cr (VI), and animals need it to maintain their metabolic processes ( Mohan and Pittman Jr, 2006 ; Urrutia et al., 2008 ). There is contradictory evidence from different research studies, on whether or not Cr is essential for plant metabolism.…”
Section: Introductionmentioning
confidence: 99%